On amorphous phase formation in dissimilar friction stir welding of aluminum to steel - Hussein, S.A. (Springer Heidelberg, 2017)
Amorphous phase which associated the joining of aluminum-to-steel via friction stir welding had been investigated in this study. AA5083, AA6061 and zinc coated steel were welded together by single pass friction stir welding. Different welding parameters of rotational and welding speeds had been used. Heat cycle measurement and scanning electron microscopy were used to investigate the effect of these welding parameter levels on the amorphous phase and intermetallic compound formations. The results showed that using of 2000 rpm with 20 mm/min as rotational and welding speeds, respectively, produced a long heat cycle. Such long heat cycle could eliminate the amorphous phase and promote thick intermetallic compounds, especially at the AA5083 to steel interface. However, when welding speed was increased to be 40 mm/min, a shorter heat cycle time was produced, and the amorphous phase was detected. Very high welding speed (300 mm/min) resulted in very short heat cycle with no obvious amorphous phase and very small amount of intermetallic compound at the aluminum-to-steel interface. The formation process of the amorphous phase is schematically explained in this study. © Springer Nature Singapore Pte Ltd. 2017.